(untitled) (World Bulletin of Social Sciences, 2023)
Acute myocardial infarctions are one of the leading causes of death in the developed world, with prevalence approaching three million people worldwide, with more than one million deaths in the United States annually. This statistic reviews the presentation, evaluation, and management of patients with acute myocardial infarctions and highlights the role of the interprofessional team in caring for these patients.